THE EXISTENCE OF TRADITIONAL CUISINE IN THE SURANADI TEMPLE AREA IN SUPPORTING SURANADI AS A CULTURAL TOURISM VILLAGE (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2025)
This study aims to identify traditional Lombok culinary products in Suranadi temple and analyze their existence in order to support the existence of Suranadi as a cultural tourism village and develop tourist attractions to encourage tourists to stay longer in Lombok. The findings are analyzed using culturaltourism theory that emphasizes the importance of preserving local culture, where traditional culinary is one of the main components that can function as a tourist attraction. This study uses a qualitative method, using interview techniques with visitors, temple managers, traders, and local community leaders, as well as conducting direct observations at the location. Traditional food products in Suranadi Temple are products from various local ingredients. These processed foods include Dodol, Pecel Lombok, Plecing, Rujak Buah Suranadi, Sate Bulayaq, and Kacang Komak Pedas. Sate Bulayaq is sold by the Muslim Sasak community, while foods other than sate bulayaq are widely sold by Hindus from the Suranadi Village area. The relevance of traditional culinary in supporting Suranadi Cultural Tourism Village is traditional food can be a unique attraction for tourists. Traditional food sold by the community can support the sustainability of tourism in Suranadi Cultural Tourism Village. From the results, the existence of traditional culinary supports the existence of cultural heritage. Suranadi traditional food can increase tourist satisfaction in enjoying the destination, impact the community's economy, and preserve Suranadi traditional food. This study has implications for traditional food development in sustainable tourist destinations in various tourist locations.
Keywords: Keywords: Dodol Suranadi: Sate Bulayaq; Tourism Village